Pemanfaatan VLAN Untuk Meningkatkan Kinerja Jaringan Komputer BKPP Kabupaten Bogor - Indriyani Widyastuti; Yayan Hendrian (LPPM Universitas Bina Sarana Informatika, 2022)
Computer networks have an important role in a government agency, especially BKPP. In their daily life, these institutions carry out activities of exchanging documents and data, printing files on the same printer and using hardware or software that is connected to the network together. Government agencies play a very important role in serving the community, therefore a good, secure, stable and fast network is needed in processing small and large data. The Bogor Regency Personnel, Education and Training Agency uses one computer that acts as a multifunctional server for the database server, DHCP server, and web server at the same time. From the results of the analysis, it was found that the topology used is an extended star with IP class C. Using a firewall that is applied to the router, as well as the default Windows antivirus that is already installed on every PC and laptop. Meanwhile, access point security uses WPA2-PSK. The problem faced is that it is easy for people from other divisions who are not interested in seeing and accessing files in other divisions that are confidential. Thus, a VLAN is needed to manage access rights between computer network users in order to maintain data and file authenticatio